Gurukula Bangli Sebagai Representasi Pendidikan Hindu Kuna - Ni Komang Sastriani (Jayapangus Press, 2018)
This paper is an description for the existence of Gurukula contained in Bangli. The Gurukula system is seen as an educational system that is represented as a form of ancient Hindu educational methods. Ancient Hindu education which has been viewed as a method that is not developed, but in fact Gurukula present as a place of education in line with Hindu literature such as Upanisad and Dharsana. It also attempts to reveal the formation of a very religious character to the sisya Gurukula through the sisya method of staying with the teacher within the prescribed time period. In addition, in this paper also reveals a moral pembentuka against sisya, so that education Gurukula can be said almost similar to informal education contained in the family. The phenomena were then dissected using the theory of Thorndike Connectionism and presented descriptively qualitatively. This paper can be a new paradigm in the planning and determination of a learning method applied in the world of education, especially Hindu religious education.